Professional Women’s Performance in Sports Journalism - Peschiera Chanamé, Lourdes (2016)
This paper aims to the analysis of Professional women’s performance in Sports Journalism, knowing the conditions, difficulties and challenges faced by feminine genre in this working field. This observation is also timely to define the space occupied Sports Journalism in Media. Communicative impact, produced by sports information, involves two dimensions: a personal nature (competitors and spectators) and a massive level (Media). Today, sport is the most widespread social activity in media and a specialized communication need in this “glocal” panorama.